Weight training steps to success - Baechle, Thomas R. 1943- (Human Kinetics, 2019)
Weight training is the most popular type of fitness training activity in the world. But if you are new to the weight room, how can you ensure you are training properly to reap the most benefits while also avoiding injury? This book takes the guesswork out of weight training and provides you with a no-nonsense approach that will guide you toward your wight training goals. Combining the experience of strength and conditioning experts, this guide will maximize your development with a progressive approach to strength training using either free weights or machines. Learn which exercises target what muscles and how to perform each one correctly and safely. Then determine the amount of weight and the number of repetitions and sets that you should lift in order to achieve your objectives. Finally, develop a workout and program that fit your interests and training preferences. Whether your goal is improving muscular endurance, building strength, increasing muscle mass, toning, or enhancing body composition, this book will help you achieve your goals.